If you build it, they may not come: Why Australian university students do not take part in outbound mobility experiences. - Jones, Benjamin; Power, Anne; Gray, Tonia; Downey, Greg; Hall, Timothy; Truong, Son (Journal of University Teaching and Learning Practice, 2016)
Universities around the world seek to internationalise students to prepare them for an increasingly globalised world. Outbound mobility experiences (OMEs) are recognised as one of the most effective ways to foster independent thinking, cultural sensitivity, and a sense of ‘worldmindedness’. This article takes a case study from an Australian university and explores efforts to increase student participation rates in OMEs. Through a mixed-method study of three student cohorts (n=223), important data was gathered relating to how OMEs are perceived by undergraduate and post-graduate students. The results are filtered through thematic discourse analysis and suggest that the university needs to do more to build awareness, explain the professional and employability benefits, and create a travel culture where students are encouraged to grow their international skills and communication competencies. This research has important implications for universities seeking to increase international student mobility and prioritise a global outlook.